ASUHAN KEBIDANAN NY “X” DENGAN PEMBERIAN HYPNOTERAPI UNTUK MENGURANGI NYERI KALA I DI PUSKESMAS BONTONYELENG - Nurul Hidayah Bohari; Ika Handayani; Silfayani; Rismayanti (Journal Of Midwifery And Nursing Studies, 2019)
Hypnobirthing is a technique of autohypnosis (self-hypnosis), which is a natural effort to instill positive intentions/suggestions into the soul/subconscious mind during pregnancy and childbirth preparation. This study aims to be able to provide care to Mrs. X by giving hypnobirthing to reduce pain in the first stage of labor at the Bontonyeleng Health Center, Bulukumba Regency. The writing method used is to collect data by interview, physical examination (hypnobirthinga0, observation, literature study, and documentation. The results show that Mrs. X after being given hypnobirthing therapy there is a decrease in pain in the first stage of normal delivery.